Chapter 5 The Biology of Entrepreneurship - Nofal, Ahmed (The Organizational Frontiers Series, 2021)
In this chapter, we provide a systematic review of the biological perspective in entrepreneurship. Specifically, we systematically review research linking the three biological strands of genetics, physiology, and neuroscience to entrepreneurship. We discuss the findings of this growing literature and how incorporating biology into the study of entrepreneurship can enhance our understanding of various entrepreneurial outcomes. We then discuss the mechanisms through which biology affects entrepreneurship. Finally, we conclude with directions for future research.